1988
DOI: 10.1007/bf02370101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhizobium inoculation on growth and nodulation ofAlbizia falcataria (L.) Fosh. andAcacia mangium Willd. in the nursery

Abstract: Three separate experiments were conducted in the nursery using grassland soil as a growing medium. The first experiment was conducted to assess the nodulation of the two legume trees grown in unamended soil, the second was done to determine the effects of N-fertilizer application on the interaction of the five Rhizobium isolates with A. falcataria and the third experiment was conducted to determine the effects of liming on the Rhizobium x A. mangium interaction.Three local Rhizobium isolates, Al6 , A~8, and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Therefore, the expected mechanisms for better PUE by the combined application of Rhizobium and P fertilization are: (1) Rhizobium inoculation with P fertilization for legumes first improves the Rhizobium N 2 fixation capacity; and (2) it then improves plant growth by improving the P acquisition characteristics of plant roots, such as improved root mass or exudate. Rondina et al [32] demonstrated that Rhizobium inoculation improved plant P uptake with increments of the root surface area, while Umali-Garcia et al [33] found similar results caused by increased root biomass. However, there is limited information about root P acquisition characteristics by root exudate, i.e., root organic acids and phosphatase activity, as well as related rhizosphere soil P dynamics under Rhizobium inoculation with P fertilization.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the expected mechanisms for better PUE by the combined application of Rhizobium and P fertilization are: (1) Rhizobium inoculation with P fertilization for legumes first improves the Rhizobium N 2 fixation capacity; and (2) it then improves plant growth by improving the P acquisition characteristics of plant roots, such as improved root mass or exudate. Rondina et al [32] demonstrated that Rhizobium inoculation improved plant P uptake with increments of the root surface area, while Umali-Garcia et al [33] found similar results caused by increased root biomass. However, there is limited information about root P acquisition characteristics by root exudate, i.e., root organic acids and phosphatase activity, as well as related rhizosphere soil P dynamics under Rhizobium inoculation with P fertilization.…”
Section: Introductionmentioning
confidence: 95%
“…To achieve maximal growth when introduced in N-deficient soils, it is recommended that A. mangium be inoculated with specific and effective strains of rhizobium, although it nodulates readily with indigenous strains of rhizobium,(10). Short-term nursery experiments performed by Umali-Gircia et al (17) showed that the inoculation of A. mangiumt with certain strains of rhizobium had a positive effect on tree biomass (expressed as total N) in nonsterile soils (Annam clay soils in the Philippines), but the authors did not specify if the effective strains belonged to the Rhizobium group or the Bradyrhizobium group. In 1990, Galiana et al (8) showed that only a restricted range of Bradyrhizobium strains were able to produce effective nodules on A. mangium and that A. mangium was a specific host since the effectiveness of these different strains varied considerably.…”
mentioning
confidence: 99%
“…Sabe-se que o N quando aplicado em pequenas doses pode beneficiar a nodulação (Ingestad, 1980;Gonçalves et al, 1999;Jesus et al, 2014). Porém, quando aplicado em doses mais altas, o N inibe a nodulação de espécies arbóreas (Umali-Garcia et al, 1988). Patreze & Cordeiro (2004) também observaram a presença de nódulos em mudas de M. bimucronata adubadas com N na forma de nitrato de amônio, em doses de 640 mg ou 320 kg N ha -1 , bastante superior ao utilizado no presente estudo.…”
Section: Figura 1a-d A)unclassified
“…Portanto, são necessárias pesquisas que comprovem a eficiência da inoculação para a grande maioria das espécies florestais (Umali-Garcia et al, 1988). Esse processo de validação possibilitará que os inoculantes sejam aprovados pelo MAPA para comercialização e disponibilizados para a sociedade.…”
unclassified